An update on immunological and molecular tests and their impact in infectious uveitis - Thomas, Joanne; Nguyen, Nam V.; Fashina, Tolulope; Huang, Ye; Yeh, Steven; Conrady, Christopher D. (Frontiers in Ophthalmology, 2023)
Early diagnosis of infectious uveitis can lead to prompt initiation of treatment to minimize vision-threatening sequelae. As various infectious etiologies of uveitis share similar clinical features, advancements in polymerase chain reaction (PCR) and metagenomic next-generation sequencing (MDS) have shown significant promise in improving diagnostic capabilities. Various techniques of PCR, including real-time, multiplex, comprehensive, and broad-range, have increased the armamentarium for infectious uveitis diagnosis. Additionally, metagenomic deep sequencing technology has provided a methodology to identify causative pathogens as well as novel etiologies of uveitis. This review discusses the diagnostic tools available for infectious uveitis and highlights the advantages and disadvantages of the techniques.